Evaluating a food safety intervention in traditional markets: A randomized controlled trial in Vietnam - Trang Le-Thi-Huyen; Hoffmann, Vivian; Murphy, Mike; Ambler, Kate; Unger, Fred; Boqvist, S.; Phuong Nguyen-Thi-Minh; Sinh Dang-Xuan; Hung Nguyen-Viet (International Livestock Research Institute, 2024)
Foodborne diseases from contaminated animal products are a significant One Health concern in low- and middle-income countries, particularly in traditional wet markets where hygiene, cross-contamination and irregular inspections pose major challenges. This study evaluated a food safety intervention in 68 traditional wet markets across five provinces in Vietnam through a randomized controlled trial.